INTEREST IN THE SOCIAL SERVICE WORK FIELD OF SPECIAL EDUCATION STUDENTS - Erma Kumala, Sari; Tias, Martika (Universitas Pendidikan Ganesha, 2019)
Students of Special Education (SE) are expected to have a high interest in the social service work field so that there is a compatibility with their education. However, the education selection of SE students is not always based on interest in the social service work field, so there is a possibility that SE students will not pursue a career in social service work field after they graduated. This study aims to determine the interest of SE students in the social service work field in the SE field. The respondents were 73 fifth semester SE students of Universitas Sebelas Maret (UNS), consisting of 54 female students and 19 male students. The sampling technique used is a non-random purposive sampling. RMIB interest test and a career interest questionnaire are used to collect the data. Data were analyzed by using frequency analysis. The results shows that (1) Based on the RMIB interest test, 79% of SE-UNS students have a high interest in the social service work field; (2) Based on the questionnaire, 60% of SE-UNS students choose to work in the social service field, such as teachers, social workers, heads of social foundations, sign language interpreters, principals, and social volunteers. Thus, it can be concluded that the majority of SE-UNS students have had interests in the social service work field in accordance with the SE field.